Model Pembelajaran Inkuiri Terbimbing dan Pengaruhya terhadap Keterampilan Proses Sains Siswa : Guided Inquiry Learning Model and Its Effect on Student Science Process Skills - Adirahayu, Mega Fauziyah; Wulandari, Fitria Eka (SEJ (Science Education Journal), 2018)
The purpose of this study is to find out whether there is an influence of the learning model Guided inquiry on the learning outcomes of science process skills of students at SMP Negeri 2 Wonoayu. The design of this study is the non-equivalent control group design. The samples used in this study were 2 classes with sampling techniques. Where from the two classes, one class is used as the experimental class, which is given treatment by using the guided inquiry learning model, while the next class is used as the control class by using the learning model that is usually used in the class. The research instrument used was a matter of science process skills with data collection techniques using the test method in the form of pre-test and post-test questions. Data analysis techniques are carried out using the "t" test. From the "t" test, the results show that there is a significant influence between the guided inquiry learning model on science process skills.